2016
DOI: 10.1111/jbi.12824
|View full text |Cite
|
Sign up to set email alerts
|

Processes underpinning fish species composition patterns in estuarine ecosystems worldwide

Abstract: Aim We present the first global biogeographical regionalization of estuaries, assessing how dispersal limitation and/or environmental filtering mechanisms drive the patterns of fish assemblage composition among and within biogeographical regions. Location Estuaries worldwide.Methods A bootstrapped hierarchical cluster analysis was applied to define biogeographical regions based on pairwise beta diversity (bsim) of fish assemblages among 393 estuaries worldwide. Variables representing dispersal limitation and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 48 publications
3
38
0
Order By: Relevance
“…Our results support a similar conclusion for the three diversity facets and revealed that changes in estuarine γ‐diversity were essentially induced by an increase of β‐diversity in large estuaries. Since entrance width and river flows are commonly used to assess the estuarine connectivity, our results are also congruent with previous findings that stress the positive effect of connectivity on fish taxonomic diversity (Henriques et al., ; Vasconcelos et al., ). Moreover, we found that the taxonomic β/α ratio was lower in shallow estuaries with high tidal range probably in response to the predominance of marine conditions at the rising tide and to the very low water level at low tide.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Our results support a similar conclusion for the three diversity facets and revealed that changes in estuarine γ‐diversity were essentially induced by an increase of β‐diversity in large estuaries. Since entrance width and river flows are commonly used to assess the estuarine connectivity, our results are also congruent with previous findings that stress the positive effect of connectivity on fish taxonomic diversity (Henriques et al., ; Vasconcelos et al., ). Moreover, we found that the taxonomic β/α ratio was lower in shallow estuaries with high tidal range probably in response to the predominance of marine conditions at the rising tide and to the very low water level at low tide.…”
Section: Discussionsupporting
confidence: 93%
“…Latitude ( Lat ., degree) was taken at the mouth of the estuary and is related to regional environmental factors, such as productivity or temperature (Henriques et al., ). The continental shelf width ( C. shelf , km) was chosen to reflect the large‐scale availability of marine habitats, as advocated by Nicolas et al.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations